2001
DOI: 10.3168/jds.s0022-0302(01)74672-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postrumen Starch Infusion on Milk Production and Energy Metabolism in Dairy Cows

Abstract: Two experiments were conducted to determine effects of postrumen starch infusion on milk production and energy and nitrogen utilization in lactating dairy cows. In experiment 1, four cows in early lactation fed grass silage and concentrates were continuously infused into the duodenum with water or 700, 1400, or 2100 g of purified maize starch daily for 10 to 12 d in a 4 x 4 Latin square design with 2-wk periods. Starch infusion increased milk yield linearly and decreased milk fat concentration in a quadratic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
69
3
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 25 publications
16
69
3
9
Order By: Relevance
“…No problem with soft faeces and diarrhoea were observed during starch infusions, and the dosage used here was lower than in other post-ruminal glucose or starch infusion studies (Hurtaud et al, 1998 andReynolds et al, 2001). In a typical Norwegian dairy cow diet, which mainly consists of grass silage and a barley/oats based concentrate mixture when cows are fed 14 to 18 kg DM, abomasal infusion of 257 to 376 g of starch will increase the post-ruminal supply by approximately 100% (Volden, 1999).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…No problem with soft faeces and diarrhoea were observed during starch infusions, and the dosage used here was lower than in other post-ruminal glucose or starch infusion studies (Hurtaud et al, 1998 andReynolds et al, 2001). In a typical Norwegian dairy cow diet, which mainly consists of grass silage and a barley/oats based concentrate mixture when cows are fed 14 to 18 kg DM, abomasal infusion of 257 to 376 g of starch will increase the post-ruminal supply by approximately 100% (Volden, 1999).…”
Section: Discussionmentioning
confidence: 76%
“…The restriction of the order of the treatments; avoiding two subsequent intravenous infusions, were done across substrates so there should be no systematic order of the substrates. Several studies have demonstrated a positive effect on milk production of infusing nutrients into the gastrointestinal tract or blood (Metcalf et al, 1996;Reynolds et al, 2001;Aikman et al, 2002). However, limited data are available comparing both post-ruminal and intravenous AA and glucose supplementation in the same experiment and animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the diet-based strategies for influencing ENU reviewed, reducing diet crude protein (CP) was the only strategy that conclusively improved ENU . Other methods to manipulate the amount, rate, and site of digestion of dietary energy have had variable effects on N utilisation despite popular theories about the effects of energy-protein synchrony and post-ruminal starch digestion (Reynolds et al 1996;Rius et al 2010). Mathematical models of N use and digestion become an important tool to investigate the discrepancy between theory and practice through identification and quantification of dietary and animal factors that influence ENU.…”
Section: Introductionmentioning
confidence: 99%